Balanoposthitis and Penile Edema. Issue 9 (September 2015) - Rovira-López, Roger; García-Martínez, Pablo; Martín-Ezquerra, Gemma; Pujol, Ramon M.; Aventín, Daniel López
<x xml:space="preserve">Abstract</x> Abstract The typical finding in primary syphilis stage is a unique, painless chancre with indurated borders. We report a case of primary syphilis presenting as erosive and crusted balanoposthitis with an underlying chancre, penile edema, and bilateral inguinal lymphadenopathy in a heterosexual man.